Efektivitas Problem Based Learning pada Pembelajaran Matematika terhadap Sikap Matematis - Erlinda Rahma Dewi; Lihar Raudina Izzati; Dita Purwinda Anggrella (Universitas Indraprasta PGRI Jakarta, 2021)
The lack of mathematical attitudes of students at SMP Negeri 2 Playen which is marked by not being ready to take part in mathematics learning and not understanding the goals and benefits of studying mathematics causes learning to be ineffective. Through PBL (Problem-Based Learning) learning is expected to provide alternative solutions so that mathematical attitudes develop optimally. Quasi-experimental (quasi-experimental) is a type of research in this study, with a non-equivalent group design pretest-posttest research design. The research instrument used a mathematical attitude questionnaire containing 25 statements with a Likert scale. As for the validity of the mathematical attitude questionnaire instrument, content validity and construct validity were carried out. The average result of the PBL class student's mathematical attitude questionnaire before treatment was 68.38, while the average result of the student's mathematical attitude questionnaire after treatment was 74.31. These results indicate an increase of 5.93. The average value of PBL class students after treatment has reached the KKM, which was a minimum score of 67.2. This was supported by the results of the SPSS one sample t-test analysis which produced a t-value of 7.725 and a significance value of 0.00. A significance value of less than 0.05 indicates that the PBL approach was effective in terms of students' mathematical attitudes.